Startle modification implications for neuroscience, cognitive science, and clinical science - Dawson, Michael E. 1940-; Schell, Anne M. 1942-; Böhmelt, Andreas H. 1963- (Cambridge University Press, 1999)
The startle response (response to a loud noise, for instance) is a reflex that is wired into the brain at a very basic level. Although everybody has such a reflex, the strength and quickness of the startle response is modified by a subject's underlying psychoneurological state. The nature of this modification, therefore, is now seen as an accurate, objective measure of very deep neurological processes. This book is a comprehensive volume devoted to startle modification and offers a unique overview of the methods, measurement, physiology and psychology of the phenomenon, particularly modification of the human startle eyeblink. Chapters are written by many of the world's leading investigators in the field and include coverage of elicitation and recording of startle blink, issues in measurement and quantification, the neurophysiological basis of the basic startle response and its modification by attentional and affective processes, psychological processes underlying short and long lead interval modification (including prepulse inhibition), applications of startle modification to the study of psychopathology, including schizophrenia, affective disorders, and psychopathy, developmental processes and relationships with ERPs and behavioural measures of information processing